Burden of liver cirrhosis in Portugal between 2010 and 2017 - Silva, João Manuel (2021)
© 2020 Sociedade Portuguesa de Gastrenterologia Published by S. Karger AG, Basel. This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY- NC-ND) (http://www.karger.com/Services/OpenAccessLicense). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.